(untitled) (Research, Society and Development, 2023)
Orofacial harmonization is a specialty in cosmetic dentistry that seeks to enhance the natural beauty of the face, offering safe and innovative procedures for facial rejuvenation. Collagen loss is an important factor in the intrinsic and extrinsic aging of the face, resulting in wrinkles and sagging. The application of collagen biostimulators, such as calcium hydroxyapatite, is an effective technique in orofacial harmonization. These biostimulators stimulate collagen production, improving skin quality, restoring volume and promoting gradual and natural rejuvenation. Professionals specialized in this technique perform precise injections in strategic areas of the face, taking into account the individual characteristics of each patient. This approach offers long-lasting results, improving the skin’s texture, firmness and elasticity. The application of collagen biostimulators is a promising option for those seeking safe and effective facial rejuvenation. Thus, the objective of this narrative review of the literature is to investigate and analyze the use of collagen biostimulators in the area of orofacial harmonization.